2014
DOI: 10.1177/0284185113512300
|View full text |Cite
|
Sign up to set email alerts
|

Utility of expiratory thin-section CT for fibrotic interstitial pneumonia

Abstract: The presence of air trapping on expiratory HRCT suggests CVD-ILD rather than IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…In a recent study, the threshold of five or more lobules of mosaic attenuation in each of three or more lobes bilaterally was found to have the highest specificity for fibrotic HP and helped differentiate this disorder from IPF ( 123 ). Because air trapping is a nonspecific finding reflecting small airway alterations of variable cause and/or severity, it is not surprising that it is also found in non-HP ILDs ( 8 ), especially connective tissue disease (CTD)-associated ILD (CTD-ILD) ( 129 ) and sarcoidosis ( 130 ).…”
Section: Radiological Featuresmentioning
confidence: 99%
“…In a recent study, the threshold of five or more lobules of mosaic attenuation in each of three or more lobes bilaterally was found to have the highest specificity for fibrotic HP and helped differentiate this disorder from IPF ( 123 ). Because air trapping is a nonspecific finding reflecting small airway alterations of variable cause and/or severity, it is not surprising that it is also found in non-HP ILDs ( 8 ), especially connective tissue disease (CTD)-associated ILD (CTD-ILD) ( 129 ) and sarcoidosis ( 130 ).…”
Section: Radiological Featuresmentioning
confidence: 99%
“…TOKURA et al [53] have reported a higher frequency of air trapping on expiratory CT scanning in rheumatoid arthritis-related ILD than in IPF, which may reflect coexisting airway disease. In addition, SONG et al [54] have shown that patients with rheumatoid arthritis are more likely to have a nontypical UIP pattern (e.g.…”
Section: Amiodarone Pulmonary Toxicitymentioning
confidence: 96%
“…15 Air trapping on expiratory CT has also been shown to be present in the majority of cases in patients with RA-ILD. 16 HRCT features of obliterative bronchiolitis also appear to be more extensive in patients demonstrating anticyclic citrullinated peptide antibody (ACCPA). 17 Follicular bronchiolitis is an exudative small airways disease characterized pathologically by bronchiolar lymphoid hyperplasia.…”
Section: Airways Diseasementioning
confidence: 99%
“…24 HRCT features of airways disease may also point the radiologist to a diagnosis of RA-ILD, with expiratory air trapping significantly more prevalent than in IPF. 16 Of patients with RA and non-UIP ILD, a nonspecific interstitial pneumonia (NSIP) or unclassifiable HRCT morphologies are the next most common phenotypes, being present in around 10 to 15% of patients. 21,25,26 Fibrotic organizing pneumonias (OPs), lymphocytic interstitial pneumonias, and desquamative interstitial pneumonias (DIPs) are rare.…”
Section: Parenchymal Diseasementioning
confidence: 99%